Answer:
G(12) = 15
Step-by-step explanation:
When doing g(x) equations, all you do is substitute the value inside the parentheses to x in the equation.
So you get 3/4(12) + 6.
Then simplify to get g(12) = 15
Answer:
<h2><u><em>
x = - 14</em></u></h2>
Step-by-step explanation:
-3x – 10 = 32 Help me I need the answer
-3x – 10 = 32
-3x = 32 + 10
-3x = 42
x = 42 :(-3)
x = - 14
-----------------
check
-3 × (-14) - 10 = 32 (remember pemdas)
42 - 10 = 32
32 = 32
the answer is good
Answer:
![y = 2x^2 + 1](https://tex.z-dn.net/?f=y%20%3D%202x%5E2%20%2B%201)
Step-by-step explanation:
The graph you see there is called a parabola. The general equation for the graph is as below
![y = a*x^2 + b](https://tex.z-dn.net/?f=y%20%3D%20a%2Ax%5E2%20%2B%20b)
To find the equation we need to find the constants a and b. The constant b is just how much we're lifting the parabola by. Notice it's lifted by 1 on the y axis.
To find a it's a little more tricky. Let's use the graph to find a value for a by plugging in values we know. We know that b is 1 from the previous step, and we know that when x=1, y=3. Let's use that!
![3 = a * (1)^2 + 1\\2 = a](https://tex.z-dn.net/?f=3%20%3D%20a%20%2A%20%281%29%5E2%20%2B%201%5C%5C2%20%3D%20a)
Awesome, we've found both values. And we can write the result.
![y = 2x^2 + 1](https://tex.z-dn.net/?f=y%20%3D%202x%5E2%20%2B%201)
I'll include a plotted graph with our equation just so you can verify it is indeed the same.
The answer would be “D” because it’s is 4 less than 7j.
Answer: 11 1/2
Step-by-step explanation: